PELATIHAN DESAIN POSTER DIGITAL KEPADA SANTRI DAN SANTRIWATI PONDOK PESANTREN BAIRUHA DI KOTA BALIKPAPAN - Pontoh, Arief Nugraha; Abdul Mujib Syadzali; Andi Akbar Hidayatullah; Muhammad Kresna Arya A; Fauzan Pachrozi Yandra; Nandiva Anindhia Apriliana; Rania Annisa Forester Bangabua; Muhammad Ryco Amanda Saputra; Ananda Aulia Hasanah (PIKAT Jurnal Pengabdian Kepada Masyarakat ITK, 2024)
Over time, as the era progresses, technology continues to evolve. The rapid pace of technological progress demands that all age groups, especially the younger generation, be willing to learn and able to utilize technology. This demands is one of the main focuses of the KKN K5 group, which is conducting community service in the form of real-world work experience at the Bairuha Islamic Boarding School in Balikpapan City. With the many students currently at Bairuha, who are part of the younger generation and a crucial age group to have knowledge and mastery of advancing technology, the KKN K5 group is motivated to organize activities that provide technological insights to the students, particularly in information technology. Given the numerous applications of information technology, the chosen activity is design training using software. The software used is Canva, which is easily accessible and offers comprehensive features for basic graphic design in digital form. Furthermore, data collection was conducted using a questionnaire to determine the impact of the training provided. From the 10 questions posed to the participants, it was concluded that the poster-making training conducted during the KKN received very positive responses from the participants. The majority of participants found the training to be interesting, beneficial, and informative.